2013
DOI: 10.5194/nhess-13-2331-2013
|View full text |Cite
|
Sign up to set email alerts
|

Sub-ionospheric very low frequency perturbations associated with the 12 May 2008 <i>M</i> = 7.9 Wenchuan earthquake

Abstract: Abstract. The present study reports the VLF (very low frequency) sub-ionospheric perturbations observed on transmitter JJI (22

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 24 publications
(42 reference statements)
0
23
0
Order By: Relevance
“…Many researchers have also performed investigations on seismo-ionospheric effects since the occurrence of the Wenchuan M S 8.0 EQ. These studies include at least ionospheric changes of ground-based ionosonde data [57][58][59][60][61][62][63][64], DEMETER satellite data [17,[65][66][67][68][69][70][71][72][73][74][75][76][77][78], ground-based GPS satellite data [17,28,57,58,74,77,[79][80][81][82][83][84], radio occultation data from six microsatellites of FORMOSAT3/COSMIC (F3/C) data [81,84,85], and CHAMP (challenging minisatellite payload) satellite data [77].…”
Section: Spatial Ionospheric Anomaliesmentioning
confidence: 99%
“…Many researchers have also performed investigations on seismo-ionospheric effects since the occurrence of the Wenchuan M S 8.0 EQ. These studies include at least ionospheric changes of ground-based ionosonde data [57][58][59][60][61][62][63][64], DEMETER satellite data [17,[65][66][67][68][69][70][71][72][73][74][75][76][77][78], ground-based GPS satellite data [17,28,57,58,74,77,[79][80][81][82][83][84], radio occultation data from six microsatellites of FORMOSAT3/COSMIC (F3/C) data [81,84,85], and CHAMP (challenging minisatellite payload) satellite data [77].…”
Section: Spatial Ionospheric Anomaliesmentioning
confidence: 99%
“…Maurya et al (2013) reported VLF (very low frequency) sub-ionospheric perturbations before the Wenchuan Earthquake. They identified a significant increase in nighttime amplitude fluctuation and dispersion 2 d prior to the earthquake.…”
Section: M79 Wenchuan Earthquakementioning
confidence: 96%
“…Short‐term prediction of their occurrence seems the possible way of their mitigation [ Hayakawa, ]. During the past three decades, utilizing ground, and satellite data, several studies related to pre‐ and post‐earthquake anomalies in the D , E , and F regions of the ionosphere together with the coseismic signatures were carried out in the direction of short time EQ forecast/precursor research [e.g., Hayakawa et al , ; Maurya et al , ; Ondoh and Hayakawa , ; Sunil et al , ]. All these wide varieties of observations are seldom consistent and often yield conflicting results even for the same earthquake.…”
Section: Introductionmentioning
confidence: 99%